The effect of supplemental arginine on the gut microbial homeostasis of broilers during sub-clinical necrotic enteritis challenge - Fathima, Shahna; Al Hakeem, Walid G.; Shanmugasundaram, Revathi; Lourenco, Jeferson; Selvaraj, Ramesh K. (Frontiers in Physiology, 2024)
Necrotic enteritis (NE) is an enteric disease of poultry that alters the structure of the gut microbial community causing dysbiosis. This experiment investigated the effects of 125% and 135% arginine diets on the gut microbial diversity and composition of broilers during a subclinical NE challenge. One hundred and twenty one-day-old chicks were randomly allocated to 4 treatments with six replicates each-Uninfected + Basal, NE + Basal, NE + Arg 125%, and NE + Arg 135% diet groups. NE was induced by inoculating 1×10 4 E. maxima sporulated oocysts on day 14 and 1×10 8 CFU C. perfringens on days 19, 20, and 21 of age. The NE challenge significantly decreased the number of observed amplicon sequence variants (p = 0.03), the abundance of the phylum Firmicutes (p < 0.01), and the species Mediterraneibacter cottocaccae (p = 0.01) in the ceca of birds on day 21. The NE challenge significantly increased the Bray-Curtis index (p < 0.01), and the abundance of the phylum Bacteroidota (p < 0.01), family Odoribacteraceae (p < 0.01), genus Odoribacter (p < 0.01), and species O. splanchnicus (p = 0.01) on day 21. During NE, the 125% arginine diet restored the abundance of Bacteroidota (p = 0.03), Odoribacteraceae (p = 0.03), Oscillospiraceae (p = 0.03), Odoribacter (p = 0.03), O. splanchnicus (p = 0.03), and M. cottocaccae (p < 0.01) on day 21. The 135% arginine diet effectively restored the loss in alpha diversity (p = 0.01) caused by NE, the abundance of Firmicutes (p = 0.01), Bacteroidota (p < 0.01), Oscillospiraceae (p = 0.03), Odoribacteraceae (p < 0.01), Odoribacter (p < 0.01), O. splanchnicus (p < 0.01), and M. cottocaccae (p < 0.01) on day 21. On day 28, the treatments had a significant effect on the cecal propionate (p = 0.01), butyrate (p = 0.04), and total SCFA (p = 0.04) concentrations. In conclusion, the 125% and 135% arginine diets restored gut microbial composition during a subclinical NE challenge, but not the cecal SCFA profile. Hence, arginine in combination with other feed additives could be used in restoring gut microbial homeostasis during NE in poultry.